Investigation of coastline change in relation to climate conditions and human activities : a case study of Ngoc Hien District in Viet Nam - Duong Thanh Thoai; Nguyen, Thi Kim Oanh; Shipin, Oleg V.; Ebbers, Theo; International Fellowships Program; Ford Foundation, USA; Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2013)
The goal of this study was to provide a better understanding of the coastline change in Ca Mau, Vietnam. The effects of climate conditions and human intervention were considered. Remote sensing technology and GIS, the time series satellite images included Landsat TM, ETM+, which cover the time frame between 1990 to2 011were used. Coastline changes, land use structures change in Ngoc Hien district of Ca Mau province were quantified and mapped out. In the study period from 1990 to 2011, Ngoc Hien area lost 2,206 ha land. The change was divided into four periods. From 1990 to 1995, this region lost 1,675 ha but gained deposited 795 ha land in period 1995 {u2013}2000, thus resulted in a net loss of 880 ha. The next period, from 2000 {u2013}2005, this region lost 617 ha land and it continued erosion 708 ha land in period 2005 {u2013}2011.During period 1990 {u2013} 2011, forest land reduced 17,952 ha while aquaculture area increased 11,933 ha. The causes of forest area change were erosion, deforestation or change in land use purpose. Area for infrastructure increased 3,092 ha. Water body increased 722 ha. There was a significant effect of coastline change on structure of land use in Ngoc Hien. Coastal zone of Ngoc Hien eroded 2,206 ha from 1990 to 2011 lead to the change in land use structure along the coast Human interventions such as deforestation, dredging rivers and construction along coastal zone were recorded as the important causes of coastline change in the study period in Ngoc Hien. In this period, the effect of climate conditions, such as rainfall, storm on coastline change were worth considering, but these climate conditions are complexly related hence could not quantified in this study. The valuation of coastal zone change, climate conditions (rainfall, storms) and human activities (deforestation, dredging river and infrastructure) were analyzed during the period which revealed similar pattern of five years average of these considered factor. The relationship between these variables existed and potentially significance. However, these may be complex and multivariate relationship that still can not be quantified using the time series analysis employed in this study. The out come of this study provided a basic for local people, decision makers to develop appropriate solutions for coastland management.
A thesis submitted in partial fulfilment of the requirements for the Degree of Master of Science in Environmental Engineering and Management
Thesis (M.Sc.) - Asian Institute of Technology, 2013
Keywords: Coasts -- Vietnam; Coast changes -- Vietnam